Epistemology of Islamic Educational Planning: An Analysis of Principles, Goals, and Values - Reyhana Nur Azizah; Melyna Wijaya Putri; Sofia Nisa Ulyantika; Romlah; Abdurrohman (Journal of Educational Management Research, 2025)
This study examines the integration of Islamic epistemology in educational planning to align traditional Islamic values ​​with the demands of modern education. The background of this research concerns the challenges posed by globalization and technological developments to education, while Islamic education faces the need to maintain the authenticity of its monotheistic values. The purpose of this study is to analyze how Islamic epistemology, encompassing revelation, reason, and experience, can be applied to adaptive, relevant educational planning. The method is a qualitative approach, grounded in primary and secondary literature, to explore fundamental theories and their applications in Islamic education. The results show that integrating revelation, reason, and experience in Islamic educational planning creates a holistic approach that is relevant to current developments. This study also found that many Islamic educational institutions still face difficulties in integrating Islamic epistemology. This study concludes that to achieve the goals of holistic Islamic education, Islamic epistemology must be integrated into educational policies and practices. The contribution of this study is to offer a more integrated model of Islamic educational planning, grounded in Islamic epistemology and relevant to global demands.